2009
DOI: 10.1142/s0219581x09006250
|View full text |Cite
|
Sign up to set email alerts
|

COMPOSITIONAL EFFECT ON THE OPTICAL ABSORPTION AND PHOTOLUMINESCENCE OFCdSxSe1-xQUANTUM DOTS EMBEDDED IN BOROSILICATE GLASSES

Abstract: The effect of composition on the optical absorption and photoluminescence (PL) spectra of the semiconductor quantum dots (QDs) of CdSxSe1-xembedded in borosilicate glass matrix has been studied. It is observed that the first exciton absorption peak shifts from 2.62 to 2.21 eV and the PL peak shifts from 2.16 to 1.87 eV as the composition of selenium increases from 8 to 92 wt%. Samples having higher concentration of sulfur are found to have higher PL peak intensity, which is interpreted to be due to high concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…It is observed that with an increase in PVA concentration from 5 to 8 wt.%, the absorption edge shifts from 3.1 to 3.6 eV. The blue shift of the absorption edge is due to an increase in quantum confinement of QDs [16,17]. The average radii of QDs are calculated using the following relation given by Barman et al [18]: 3) represents the kinetic energy of the confined exciton and the second term (II) is the Coulomb interaction of the electron with the hole.…”
Section: Resultsmentioning
confidence: 97%
“…It is observed that with an increase in PVA concentration from 5 to 8 wt.%, the absorption edge shifts from 3.1 to 3.6 eV. The blue shift of the absorption edge is due to an increase in quantum confinement of QDs [16,17]. The average radii of QDs are calculated using the following relation given by Barman et al [18]: 3) represents the kinetic energy of the confined exciton and the second term (II) is the Coulomb interaction of the electron with the hole.…”
Section: Resultsmentioning
confidence: 97%